Implementasi Education Management Information System (EMIS) dalam Mengelola Data Lembaga di Kementerian Agama Lamongan untuk Meningkatkan Efektivitas Administrasi Pendidikan - Nur Fitria; Sahudi Sahudi; Arif Mansyuri (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study discusses the implementation of the Education Management Information System (EMIS) in managing educational institution data at the Ministry of Religious Affairs of Lamongan Regency to improve the effectiveness of educational administration. EMIS is a technology-based information system used to manage educational data in an integrated manner, including institutional data, students, educators, as well as facilities and infrastructure. The implementation of EMIS aims to improve the quality of administrative management so that it becomes faster, more accurate, and more efficient compared to manual systems. In addition, EMIS also facilitates reporting processes, data validation, and data-based decision-making in a more precise, transparent, and structured manner. The implementation of EMIS at the Ministry of Religious Affairs of Lamongan Regency also supports digital transformation in Islamic education management in the modern era. Although there are still several challenges in its implementation, such as limited technological infrastructure, internet networks, and operator capabilities, this system continues to provide significant positive impacts on improving the quality of educational administrative services. Thus, EMIS becomes an important solution in realizing effective, efficient, and accountable educational governance.